Atom transfer radical polymerization of 1-phenoxycarbonyl ethyl methacrylate monomer - Demirelli, K; Kurt, A; Coskun, M (Pergamon-Elsevier Science Ltd, 2004)
Atom transfer radical polymerization conditions with copper(I) bromide/2,2'-bipyridine (Cu/2,2'-bpy) as the catalyst system were employed for the homopolymerization and random copolymerization of 1-phenoxycarbonyl ethyl methacrylate (PCMA) with methyl methacrylate (MMA). Temperature studies indicated that the polymerizations occurred smoothly in bulk at 110 degreesC. Poly(PCMA)(polydispersity index = 1.27) homopolymer was characterized and then used as macroinitiator for increasing its molecular weight. The homopolymerization of PCMA was also carried out under free radical conditions using 2,2'-azobisisobutyronitrile as an initiator. The monomer and polymers were characterized by FT-IR and H-1 and C-13-NMR techniques. The glass transition temperatures, the solubility parameters and average-molecular weights of the polymers were determined. Thermal stabilities of the polymers were given as compared with each other by using TGA curves. Thermal degradation products of poly(PCMA)s obtained by ATRP and free radical polymerization were compared with each other by using H-1-NMR technique. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: synthesis; atom transfer radical polymerization (ATRP); thermal degradation